Component recommendation for development of composite consumer applications : : doctoral thesis - Budiselić, Ivan 1985 (I. Budiselić ; Fakultet elektrotehnike i računarstva, 2014)
SUMMARY: Consumer computing is a research area that focuses on methodologies and tools that enable consumers to create their own applications. Consumers create applications by composing existing applications through intuitive actions on their graphical user interfaces. Support for component discovery has been identified as a key challenge in various forms of composite application development, and is especially important in consumer computing. This dissertation introduces a general method for component recommendation based on structural similarity of compositions which dynamically ranks and recommends components as a composite consumer application is being incrementally developed by structurally comparing the partial composition with a database of previously completed compositions. Using this method, four component recommender algorithms are defined. Accuracy, coverage and response time of the presented algorithms are evaluated in detail on a Yahoo Pipes dataset and a synthetic dataset that models more complex composite consumer applications. The results show that the presented approach is effective in addressing the component discovery challenge in consumer computing. The scientific contributions of the doctoral thesis are a set of models for composite application structure, a framework for component recommendation based on composition structural similarity, a set of component recommender algorithms and the evaluation of this proposed set of algorithms on precision, recall, execution time and other recommender success measures. -